Histopatologi Testis pada Tikus Putih (Rattus norvegicus) yang Diberikan Minyak Jelantah dan Infusa Teh Hitam (Camellia sinensis) - Gina Fendiati Putri; Liya Agustin Umar; Elvira Yunita (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2021)
This study aimed to analyze the effect of infusion of black tea (Camellia sinensis) on the histopathological features of the testes in white rats (Rattus norvegicus) that had been induced with used cooking oil. The design of this research is an experimental post-test only control group design. The research subjects used 24 rats which were divided into six groups with six weeks of treatment. The testicular condition was assessed using the Johnsen Score criteria. The results of this study indicate that there are differences in testicular damage scores between treatment groups. The results of the histopathological score analysis showed that the group that was given only used cooking oil had a higher level of damage than the group that was only given black tea. The group that was given cooking oil and black tea one hour later affected testicular damage in rats with p significance values ​​of 0.018 and 0.018. In conclusion, giving black tea infusion at a dose of 0.50 g/200 gram BW and 0.75 gr/200 gram BW was able to prevent damage due to oil induction with 12x heating in the testes of Rattus norvegicus rats. Keywords: Camellia sinensis, Histopathology, Cooking Oil, Rat Testes